2014
DOI: 10.1038/am.2013.72
|View full text |Cite
|
Sign up to set email alerts
|

Electric control of straight stripe conductive mixed-phase nanostructures in La-doped BiFeO3

Abstract: This study examines the atomic force microscope (AFM) tip-based electrical formation of tens of microns long stripe (and B100 nm wide) inorganic one-dimensional nanostructures based on the morphotropic phase boundary of La-doped BiFeO 3 epitaxial thin films. The substitution of Lanthanum into bismuth ferrite not only produces the formation of straight stripe mixedphase patterns but also improves the spatial continuity drastically by two orders of magnitude. We create, switch and erase stripe nanostructures in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 35 publications
5
45
0
Order By: Relevance
“…1(b,d). Based on earlier published reports223033, the polarization of the R-like phase is tilted away from the surface normal compared to the nearly vertical orientation in the T-like phase. Therefore, the structural transformation as observed (“event #1”) in Fig.…”
Section: Resultsmentioning
confidence: 84%
“…1(b,d). Based on earlier published reports223033, the polarization of the R-like phase is tilted away from the surface normal compared to the nearly vertical orientation in the T-like phase. Therefore, the structural transformation as observed (“event #1”) in Fig.…”
Section: Resultsmentioning
confidence: 84%
“…Doping of BFO in general offers attractive features that can alter the material's properties in technologically relevant ways, 17,24,25 particularly with respect to domain wall and phase boundary conductivity. 26,27 More specifically, the introduction of cobalt into the BFO structure has been predicted to induce discrete high and low spin states 28 and through this mechanism increase the magnitude of the weak magnetic moment. 29 It has also been shown that doping BFO nanoparticles with cobalt can have significant effects on the magnetic and magnetoelectric behavior.…”
Section: © 2018 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%
“…By performing a systematic angle-resolved piezoresponse force microscopy (PFM) study in BLFO thin films on LAO substrates, Kim et al argued that a slow-scan direction during PFM-based electrical poling determines the major elongation axis of MPBs and it is possible to create uniform long-and-straight stripes [16]. By virtue of the excellent MPB controllability of BLFO thin films, we have been able to survey a correlation between the MPB elongation axis and its in-plane AFM spin axis.…”
Section: Introductionmentioning
confidence: 99%